2019
DOI: 10.3389/fmicb.2019.01199
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of Nucleic Acids by a Cystic Fibrosis Pseudomonas aeruginosa Isolate: An Adaptive Pathway to Cystic Fibrosis Sputum Environment

Abstract: Pseudomonas aeruginosa is a major cause of morbidity and mortality in patients with cystic fibrosis (CF). We undertook Biolog Phenotype Microarray testing of P. aeruginosa CF isolates to investigate their catabolic capabilities compared to P. aeruginosa laboratory strains PAO1 and PA14. One strain, PASS4, displayed an unusual phenotype, only showing strong respiration on adenosine and inosine. Further testing indicated that PASS4 could grow on DNA as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…This adaptation may be a double-edged sword because, while it contributes to high fitness in the CF airways, it also limits the potential to move to other environments, where nutrients are scarce [ 285 ]. A recent study showed that a CF isolate was only able to use purines and DNA as carbon sources, likely as an adaptation to the availability of eDNA in the CF environment [ 286 ].…”
Section: Bacterial Adaptation Within the Lungmentioning
confidence: 99%
“…This adaptation may be a double-edged sword because, while it contributes to high fitness in the CF airways, it also limits the potential to move to other environments, where nutrients are scarce [ 285 ]. A recent study showed that a CF isolate was only able to use purines and DNA as carbon sources, likely as an adaptation to the availability of eDNA in the CF environment [ 286 ].…”
Section: Bacterial Adaptation Within the Lungmentioning
confidence: 99%
“…Auxotrophy or reduction of catabolic capacities are frequently observed and arise from either low or high molecule availability in the CF environment. Amino acid auxotrophy often arises in CF-adapted P. aeruginosa due to the high abundance of these molecules in CF sputum [107,[110][111][112]; in addition, purine auxotrophy can be established in DNA-rich sputa [113]. Development of new metabolic capacities can nonetheless arise through enrichment of the accessory genome in metabolic functions [17,28,60].…”
Section: Metabolic Alterationsmentioning
confidence: 99%
“…We detected a concentration-dependent reduction of growth rate as the CIP concentration was increased, similar to another study with CIP in P. aeruginosa 12 . We then employed RNA-Seq analysis to investigate the influence of a sub-inhibitory CIP concentration on the gene expression of PaeAG1 and its relationship with the bacterial growth, similar to recent studies in P. aeruginosa 76 , 77 and other bacteria 16 , 44 , 78 81 . Differential expression analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This profile is associated with tolerance to oxidative stress, iron availability, biofilms, virulence and killing microbial competitors 109 . Phenazine biosynthesis is regulated by the Rhl 76 and PQS 110 quorum sensing systems in P. aeruginosa . The rhlR gene was found to be up-regulated, suggesting a possible regulation of the phenazines.…”
Section: Discussionmentioning
confidence: 99%